Indigenous Knowledge and Practices in the Management of Sickle Cell Anaemia among the Yorùbá in Osun State, Nigeria - Musediq Olufemi Lawal (Etnoantropološki Problemi, 2019)
This study is an ethnological and anthropological appreciation of indigenous approach in the management of Sickle Cell Anaemia (SCA) among the Yorùbá in Southwestern Nigeria. I adopted qualitative methods (oral interview, key informant investigation) to source for primary data from the respondents. Convenience, purposive and snowball sampling methods were utilized in the selection of the study settings and the population. At the end, 44 respondents were sampled. The study population included the herbalists, Christian and Islamic Clergies, primary caregivers to the people living with SCA. Data collected were analysed using open code software package and ethnographic summaries. Important quotations from respondents during IDI and KII sessions were reported verbatim for further illustration of issues under focus. The findings demonstrated the ingenuity of Africans in using ethnomedical and spiritual healings to overcome the seemingly unending crises and accompanied excruciating pains in this disorder. Steps toward the usage started with interpretation of SCA which was heavily influenced by interpersonal relationship. Choices of treatment facilities were made out of available options. Occasionally, healing methods were combined in line with environmental dictates. Such combination included home remedies and hospital care. Traditional medicine and faith-based healing were most favoured by those who utilized more than one healthcare source. Herbal therapies, faith-based care, divination and home remedies received better patronage in the rural area. Continuous usage and perceived efficacy of these approaches therefore shows that the people have adequate knowledge of Sickle Cell Anaemia and a need for further appreciation of folkway in healing process.